2019
DOI: 10.3390/infrastructures4010004
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Driving Factors Causing Urban Expansion in the Peri-Urban Areas Using Logistic Regression: A Case Study of the Greater Cairo Region

Abstract: The peri-urban area (PUA) of the Greater Cairo Region (GCR) in Egypt has witnessed a rapid urban expansion during the last few years. This urban expansion has led to the loss of wide, areas of agriculture lands and the annexation of many peripheral villages into the boundary of the GCR. This study analyzed the driving factors causing the urban expansion in the GCR during the period 2007–2017 using the logistic regression model (LRM). Eight independent variables were applied in this model: distance to the neare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 36 publications
3
21
0
Order By: Relevance
“…The strong influence of the factor of proximity to main roads on urban expansion in Delhi was similar to its influence in other cities, such as Cairo in Egypt and Atlanta in Georgia [56][57][58]. This result is also in line with previous results presented by Sharma in 2013, who found that the ribbon growth pattern along roads was the dominant pattern of urban expansion when monitoring the urban dynamics in Delhi from 1998 to 2011 [26].…”
Section: The Logistic Regression Analysissupporting
confidence: 89%
“…The strong influence of the factor of proximity to main roads on urban expansion in Delhi was similar to its influence in other cities, such as Cairo in Egypt and Atlanta in Georgia [56][57][58]. This result is also in line with previous results presented by Sharma in 2013, who found that the ribbon growth pattern along roads was the dominant pattern of urban expansion when monitoring the urban dynamics in Delhi from 1998 to 2011 [26].…”
Section: The Logistic Regression Analysissupporting
confidence: 89%
“…Therefore, the urban densities in the peripheral municipalities are considered very high. On the other hand, the quantitative analysis of the crowding data indicated that reason for this decline most probably because of the increasing numbers of the vacant houses in the PUA due to real estate speculation in these areas where the percentages of vacant houses reach 22.7 % of the total number of apartments [59].…”
Section: Built Environmentmentioning
confidence: 99%
“…The goodness of the MLR fit is expressed by the relative operating characteristic (ROC) coefficient, according to which values of the coefficient are between 0.5 (random fit) and 1 (perfect fit) (Pontius Jr & Batchu, 2003;Pontius & Schneider, 2001). A multicollinearity test, variance inflation factor (VIF), was performed to verify that there are no driving forces measuring the same phenomenon among all the independent variables (Belsley, 1991;Montgomery & Runger, 1994;Salem et al, 2019). The presence of multicollinearity between the variables is expressed by VIF values greater than 4.…”
Section: Transition Potential and Calibration Processmentioning
confidence: 99%